Are local governments more efficient as the same political coalition governs? A study among Chilean municipalities - Martínez José; Salazar César; Améstica-Rivas Luis (Estudios de Economía, 2020)
Lately, questionings have emerged on how public resources are managed. This work calculates the technical efficiency of municipalities in Chile, with special emphasis on the political factors that drive efficiency in the management of local resources. In particular, focus is placed on the relationship between political ideology of the local government and central government. To do this, we use a panel data of Chilean municipalities for the years 2010-2016. The methodology follows two stages. First, we estimate efficiency scores by the Data Envelopment Analysis (DEA) approach. Second, a Fractional Probit model is estimated to explain these scores. The main results show that, on average, municipalities produce 49% achieve 49% less of output than the optimal. Higher levels of efficiency are obtained in larger, urban communes and with greater participation in the Municipal Common Fund. Efficiency increases when the mayor presents himself for a re-election and is reduced in the periods in which a left coalition governs. The later effect is reduced to the extent that the majority of the municipal council share the same ideology of the national government, suggesting an effect of the relationship between the central and local government on efficiency levels.